Reuse of drugs for COVID-19: advisable or not? (Research, Society and Development, 2021)
With the COVID-19 pandemic, the need for the search for medicines for the treatment and prevention of the disease arose. Consequently, some drugs were reused. Thus, the present study aimed to conduct a review of the drugs chloroquine, hydroxychloroquine and ivermectin, highlighting the mechanisms of action, studies that prove- or not- their efficacy goes to SARS-CoV-2 and the main adverse effects related to irrational use, understanding whether the use of these drugs should be advised or not. The literature review was based on scientific articles indexed in the Pubmed databases and Portal of Capes Journals published in the last 3 years, using the descriptors "Use of medicines"; "COVID-19"; "Self-medication" and "Rational use of". From the analysis of 27 articles, it was found that many in vitro and clinical studies were conducted, however, they are controversial. Thus, the use of these drugs in an irrational way, as has been occurring, brings health risks. It is necessary to have more complex and serious clinical studies in case of a non-conflicting result being taken as a reference.